ChemInform Abstract: Lithium Containing Rare‐Earth Metal Germanide, Er3.93Li1.07Ge4: Synthesis, Crystal Structure and Chemical Bonding. Issue 33 (25th July 2013) - Nam, Gnu; Jeon, Beom Yong; Kim Youngjo, Kim Youngjo; Kang, Sung Kwon; You, Tae‐Soo
Abstract The title compound is prepared from a stoichiometric mixture of the elements (sealed Nb ampule, 1080 °C, 5 h and 750 °C, 2 d) and characterized by single crystal XRD and TB‐LMTO computations.